Accurate high‐resolution single‐crystal diffraction data from a Pilatus3 X CdTe detector. Issue 3 (23rd April 2020) - Krause, Lennard; Tolborg, Kasper; Grønbech, Thomas Bjørn Egede; Sugimoto, Kunihisa; Iversen, Bo Brummerstedt; Overgaard, Jacob
Abstract : Detailed analysis of the high‐flux deficiencies of pixel‐array detectors leads to a protocol for the measurement of structure factors of unprecedented accuracy even for inorganic materials, and this significantly advances the prospects for experimental electron‐density investigations. Abstract : Hybrid photon‐counting detectors are widely established at third‐generation synchrotron facilities and the specifications of the Pilatus3 X CdTe were quickly recognized as highly promising in charge‐density investigations. This is mainly attributable to the detection efficiency in the high‐energy X‐ray regime, in combination with a dynamic range and noise level that should overcome the perpetual problem of detecting strong and weak data simultaneously. These benefits, however, come at the expense of a persistent problem for high diffracted beam flux, which is particularly problematic in single‐crystal diffraction of materials with strong scattering power and sharp diffraction peaks. Here, an in‐depth examination of data collected on an inorganic material, FeSb2, and an organic semiconductor, rubrene, revealed systematic differences in strong intensities for different incoming beam fluxes, and the implemented detector intensity corrections were found to be inadequate. Only significant beam attenuation for the collection of strong reflections was able to circumvent this systematic error. All data were collected on a bending‐magnet beamline at a third‐generation synchrotron radiation facility, so undulator and wiggler beamlines and fourth‐generation synchrotrons will be even more prone to this error. On the other hand, the low background now allows for an accurate measurement of very weak intensities, and it is shown that it is possible to extract structure factors of exceptional quality using standard crystallographic software for data processing ( SAINT‐Plus, SADABS and SORTAV ), although special attention has to be paid to the estimation of the background. This study resulted in electron‐density models of substantially higher accuracy and precision compared with a previous investigation, thus for the first time fulfilling the promise of photon‐counting detectors for very accurate structure factor measurements.